EVALUASI PELESTARIAN ARSITEKTUR POS BLOC JAKARTA - Padraic Harianto, Jose; S.Sombu, Alwin (Riset Arsitektur (RISA), 2025)
Abstract -Jakarta has many historical buildings that become cultural heritage, one of them is the Jakarta Bloc Post Building.The Post Bloc Jakarta Building as a class A cultural heritage building is currently experiencing a significant change in function , therefore it needs to be further investigated how the impact of the current transition of function on the preservation of its architecture in terms of aspects of form and construction. This study utilizes a descriptive analysis - evaluative methodology. The construction aspect of the Pos Bloc Jakarta building involving alterations in its present function has maintained its authenticity, whereas the form aspect has undergone several modifications. Through the replacement of doors and windows on the facade and the addition of extensions to the right wing mass, significant changes have been made to the building's mass and facade. As an adaptation to present functions, the building's form has also changed significantly, with retail space added to the main hall, the layout of the right and left wing masses changed, as well as various door and window features. According to the findings of these adjustments, which were analyzed using the conservatory guidelines, some significant changes to the architectural components of doors, windows on the facade, and internal space were not permitted under the preservation law. The evaluation results have suggested preservation actions on aspects of shape and construction that still retain their original characteristics.Reconstruction actions of doors and windows on the facade to restore the original character and characteristics of the building facade. Adaptation action on building interior as a form of adjustment to its current function. Keywords : Conservation , Form , Function , Construction , Pos bloc Jakarta